Digital health applications, telemedicine and large language models in dermatology: results of a Germany-wide survey - Henk, Lukas; Schirren, Leah; Mühlensiepen, Felix; Traidl-Hoffmann, Claudia; Otten, Marina; Olsavszky, Victor; Zink, Alexander; Hertl, Michael; Kuhn, Sebastian; Knitza, Johannes (Journal der Deutschen Dermatologischen Gesellschaft, 2026)
Background: Digital technologies offer opportunities for dermatological care, but there is a lack of systematic data on their use and acceptance, particularly with regard to digital health applications (DiGA) and large language models (LLMs). Patients and Methods: From November 2024 to January 2025, an anonymous online survey was conducted among German dermatologists as part of continuing education courses. The survey covered the use of and attitudes towards telemedicine, DiGA and LLMs, as well as competence assessments and education needs. Results: 100 dermatologists participated (64% female, average age 40.6 years). 58% stated that they did not currently offer telemedicine services; only 5% regularly used video consultations. 21% had already prescribed DiGA, with the majority (78%) seeing this as the responsibility of general practitioners. 96% of dermatologists believed that DiGA could improve medical care. The main barriers cited were lack of knowledge (76%), lack of time (74%), insufficient remuneration and a complex prescription process (43% each). 45% of respondents had used LLMs in a professional context. 76% rated the impact of digitalization on patient care as positive, and 80% expressed a desire for training opportunities on the use of digital technologies in everyday medical practice. Conclusion: Digitalization and, in particular, DiGA are viewed positively by most dermatologists, but digital services are hardly used at present. Targeted knowledge expansion and specific training opportunities could significantly promote the implementation of digital technologies in everyday dermatological practice.
Erstmals veröffentlicht: 19. Januar 2026
Gesehen am 10.02.2026